Terrestrial Molluscs of the Genus Pseudonapaeus and Chondrulopsina of the Buliminidae Family in Mirzachol (Eurasian Scientific Herald, 2023)
The article is based on the results of many years of research, and the area and population density of land molluscs of the family Buliminidae in Mirzachol, the genus Pseudonapaeus and Chondrulopsina, are scientifically justified. Ecological-taxonomic structure, distribution, biology and processes of change in them, as well as economic importance of gastropod molluscs of Mirzachol natural geographical region were studied. Each of the gastropod molluscs has its own biological characteristics.